2022
DOI: 10.1111/desc.13253
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a developmental shift in the motivation underlying helping in early childhood

Abstract: We investigated children's positive emotions as an indicator of their underlying prosocial motivation. In Study 1, 2-, and 5-year-old children (N = 64) could either help an individual or watch as another person provided help. Following the helping event and using depth sensor imaging, we measured children's positive emotions through changes in postural elevation. For 2-year-olds, helping the individual and watching another person help was equally rewarding; 5-year-olds showed greater postural elevation after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Thus, children's rejection of advantageous unfairness may not exclusively depend on a negative emotional response to outcomes that disadvantage others, but require additional strategic motivations. On the other hand children's negative emotional response to disadvantaging others may not depend on similar strategic concerns (see [ 52 ], although see also [ 90 ]). To test this possibility, future studies should examine whether children's emotional expression and behaviours in response to advantageous inequity are influenced by comparable strategic motives.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, children's rejection of advantageous unfairness may not exclusively depend on a negative emotional response to outcomes that disadvantage others, but require additional strategic motivations. On the other hand children's negative emotional response to disadvantaging others may not depend on similar strategic concerns (see [ 52 ], although see also [ 90 ]). To test this possibility, future studies should examine whether children's emotional expression and behaviours in response to advantageous inequity are influenced by comparable strategic motives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both children and zoo or sanctuary-living captive chimpanzees demonstrate proclivities to help others at early ages in similar experimental contexts ( Warneken and Tomasello, 2006 , Greenberg et al, 2010 , Yamamoto et al, 2012 ). However, by five years of age children’s positive emotions when helping others appear enhanced by an audience, a factor that does not affect the positive emotions of 2-year-old children in the same experiment ( Hepach et al, 2022 ). Another experimental study showed that 5-year-old children but not chimpanzees (who ranged in age) were more likely to share and less likely to steal from others when a peer watched them compared to when unobserved, suggesting that reputational concerns influenced children’s but not chimpanzees’ prosocial proclivities ( Engelmann et al, 2012 ).…”
Section: Why Are Wild Chimpanzees Useful Models For Understanding Ado...mentioning
confidence: 99%
“…As we have discussed, adolescent and adult males may take on a caretaking role of orphaned youngsters who are often their maternal siblings ( Box 3 , Reddy and Mitani, 2019 ). But there is minimal evidence of biological fathers playing a caretaking role ( Boesch et al, 2006 , Hepach et al, 2022 ). Given the mating system of chimpanzees, where females mate with multiple males, it is expected that male chimpanzees cannot identify their offspring and offspring cannot identify their biological fathers.…”
Section: Social Motivation and Experiences In Chimpanzee Adolescence:...mentioning
confidence: 99%
“…To resolve these issues, in the present work, we directly test children's behavior toward ingroup and outgroup members at ages when social desirability concerns have not yet emerged (Fu et al, 2016;Hepach et al, 2017Hepach et al, , 2022Warneken & Tomasello, 2013). In Study 1, we examine toddlers' resource allocations toward ingroup and outgroup members.…”
Section: Ingroup Positivity and Outgroup Negativity Jointly Motivate ...mentioning
confidence: 99%